Pelatihan Perancangan Komputer Akuntansi Koperasi Simpan Pinjam Berdasarkan Standar Akuntansi Keuangan Entitas Privat di DKI Jakarta - Firdaus, Evan; Nurpadi, Dady (LPPM Universitas Koperasi Indonesia, 2024)
SP/USP Cooperative Accounting Computer Training Activities based on Private Entity SAK strengthened by Permenkop UKM No.2 of 2024 are very necessary because they will come into effect in 2025, the use of computerization speeds up work in accounting processing more effectively and efficiently. This training has the theme Digital Transformation Towards Modern Cooperatives, one of which is in the field of Computerized Cooperative Accounting using the Myob Accounting application, where the steps are 18 steps starting from (1) Creating Cooperative Data; (2) Accounting Period; (3). Build Your Account List; (4).Assistant Account: (5). Creating Account Flats: (6): Creation of Asset, Liability, Equity, Income and Expense Accounts; (7). Entering Initial Balance (Trial Balance): (8). Creating Data Customer (borrower) and Supplier (storage); (9) Borrower creation starts from filling in the application profile; (10) Menu Fill in Borrower's Initial Balance; (11). Creating an Initial Savings Balance; (12). Make Linked Account; (13) Create a Tax Code; (14). Recording of savings and loan transactions; (15). Recording Principal, Mandatory, Voluntary, etc. Savings Transactions; (16). Savings Transactions with Banking; (17). Cash Payment Transactions (GJ); (18). Bringing up Financial Reports